2002
DOI: 10.1007/s11746-002-0500-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of droplet size on lipid oxidation rates of oil‐in‐water emulsions stabilized by protein

Abstract: In emulsions lipid oxidation is mainly influenced by the properties of the interface. The aim of this work was to investigate the effects of droplet size and interfacial area on lipid oxidation in protein-stabilized emulsions. Emulsions, made of stripped sunflower oil (30% vol/vol) and stabilized by BSA were characterized by surface area values equal to 0.7, 5.1, and 16.3 m 2 ·cm −3 oil. The kinetics of O 2 consumption and conjugated diene (CD) formation, performed on emulsions and nonemulsified controls, show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
99
2
3

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 166 publications
(118 citation statements)
references
References 19 publications
10
99
2
3
Order By: Relevance
“…A general belief is that small particle size increases surface area and thus increases the chance of oil droplet being contacted with pro-oxidant transition metal ions, leading to fast lipid oxidation (2,17). Others reported that particle size of oil droplets did not affect lipid oxidation rate of o/w emulsion (18,19), or decreased particle size improved oxidative stability of various o/w emulsion (20). Our study seems to suggest that particle size did not significantly affect PL oxidation.…”
Section: Resultssupporting
confidence: 39%
“…A general belief is that small particle size increases surface area and thus increases the chance of oil droplet being contacted with pro-oxidant transition metal ions, leading to fast lipid oxidation (2,17). Others reported that particle size of oil droplets did not affect lipid oxidation rate of o/w emulsion (18,19), or decreased particle size improved oxidative stability of various o/w emulsion (20). Our study seems to suggest that particle size did not significantly affect PL oxidation.…”
Section: Resultssupporting
confidence: 39%
“…Development of oxidation was followed by measurement of oxygen consumption by the ground meat productemulsion mixtures kept in closed vials at 37°C in the dark. Oil-in-water emulsions were prepared with safflower oil (30 g oil; SICTIA) and 10 g/L bovine serum albumin (ICN Biochemicals, Inc.) in 0.1 mol/L sodium phosphate buffer (pH 6.0) and 0.2 g/L NaN 3 as previously described (27,28). The mean surface diameter (d 3,2 ) of droplets was ∼1 μm.…”
Section: Characterization Of Processed Meatsmentioning
confidence: 99%
“…These results suggest that the depletion of antioxidants, by itself, does not trigger the onset of oxidation; if it did, pure emulsified lipids would be instantaneously oxidized in the absence of antioxidants. Nevertheless, many studies in the literature have reported that lipid oxidation does start immediately under certain circumstances, especially when pro-oxidative catalysts are added (Sy et al 2015, Yoshida & Niki 1992 or when oxidative conditions, such as the combination of temperature and high-pressure homogenization, are used (Cuvelier et al 2003, Lethuaut et al 2002. Therefore, in practice, numerous reported examples of oxidation kinetics do not show the normal lag phase.…”
Section: Introductionmentioning
confidence: 99%